Role of genetic variants and host polymorphisms on COVID‐19: From viral entrance mechanisms to immunological reactions. Issue 5 (8th February 2022) - Adli, Abolfazl; Rahimi, Mandana; Khodaie, Reza; Hashemzaei, Niloofar; Hosseini, Sayed M.
Abstract: Coronavirus disease 2019 (COVID‐19), caused by a highly pathogenic emerging virus, is called severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Knowledge regarding the pathogenesis of this virus is in infancy; however, investigation on the pathogenic mechanisms of the SARS‐CoV‐2 is underway. In COVID‐19, one of the most remarkable characteristics is the wide range of disease manifestation and severity seen across individuals of different ethnic backgrounds and geographical locations. To effectively manage COVID‐19 in the populations, beyond SARS‐CoV‐2 detection, serological response assessment, and analytic techniques, it is critical to obtain knowledge about at‐risk individuals and comprehend the identified variations in the disease's severity in general and also in the populations' levels. Several factors can contribute to variation in disease presentation, including population density, gender and age differences, and comorbid circumstances including diabetes mellitus, hypertension, and obesity. Genetic factors presumably influence SARS‐CoV‐2 infection susceptibility. Besides this, COVID‐19 has also been linked with a higher risk of mortality in men and certain ethnic groups, revealing that host genetic characteristics may affect the individual risk of death. Also, genetic variants involved in pathologic processes, including virus entrance into cells, antiviral immunity, and inflammatory response, are not entirely understood. Regarding SARS‐CoV‐2 infection characteristics, the present review suggests that various genetic polymorphisms influence virus pathogenicity and host immunity, which might have significant implications for understanding and interpreting the matter of genetics in SARS‐CoV‐2 pathogenicity and customized integrative medical care based on population investigation. Highlights: Genetic factors presumably influence SARS‐CoV‐2 infection susceptibility. Genetic variants were involved in the pathologic processes of SARS‐CoV‐2 infection. Various genetic polymorphisms influence virus pathogenicity and host immunity. Human leukocyte antigens (HLAs) may play a vital role in SARS‐CoV‐2 susceptibility. Polymorphisms in several genes such as IL‐6, TMPRSS2, IFITM3, CD26, ACE, and DBP were associated with the COVID‐19 severity.